Urgensi angka harapan sekolah anak sebagai upaya pembangunan sumber daya manusia di Provinsi Papua - Navoleon, Alfaridho; Muljanto, Muhammad Agus (Co-Creation : Jurnal Ilmiah Ekonomi Manajemen Akuntansi dan Bisnis, 2023)
Papua Province, as one of the outermost and foremost regions in Indonesia, still faces various challenges in improving access to and quality of education for its children. The School Expectancy Score (AHS) for completing a certain level of education can be an important indicator for understanding the level of education in an area. This research aims to reveal the urgency of children's AHS as an effort to develop human resources in Papua Province. The research method used is a qualitative approach with secondary data collection. Data analysis was carried out to evaluate trends and patterns of AHS in Papua Province over the last few years, as well as identify factors that influence AHS. The research results show that AHS in Papua is still low compared to the national average, indicating a significant education gap between Papua Province and other regions in Indonesia. Factors such as inadequate educational infrastructure, high levels of poverty, social conflict, and cultural diversity are the main obstacles to achieving increased AHS in Papua New Guinea. It can be concluded that increasing children's AHS in Papua Province has high urgency in human resource development efforts. By overcoming these obstacles, Papua Province can encourage wider educational participation and improve the standard of living of its people.